Strobilanthes jomyi (Acanthaceae), a remarkable new species from South India - Biju, Punnakot; Josekutty, Elayanithottathil Joseph; Rekha, Damodaran; Wood, John R.i. (Phytotaxa, 2017)
A new species, Strobilanthes jomyi, is described and illustrated from Kerala, India. The new species is similar to S. ixiocephala in its spheroidal, echinulate pollen, but differs in its pendulous inflorescence, thinly hispid style, exserted stamens and 4-seeded capsule with entirely pubescent seeds. It is also similar to S. ciliata in the form of its inflorescence and exserted stamens and style, but differs in its ovate-elliptic leaves with crenate margin, hairy bracts and bracteoles, glandular-pubescent ovary and gland-tipped capsule, pubescent seeds and spheroidal, echinulate pollen. Its possible relationships are discussed based on its pollen and floral morphology.